A Unified Measure of Media Brand Personality: Developing A Media Brand Personality Scale for Multiple Media. Issue 3 (3rd July 2017) - Kim, Danny D. E.
ABSTRACT: The macro versus micro debate in the brand personality literature has yielded a variety of micro approach brand personality scales for different media, with both differences and parallels in personality dimensions uncovered. The observed parallels in media brand personality dimensions and the varying media contexts under which empirical tests of selective exposure theories have been conducted suggest some common ground in the way that media product brands of different formats are perceived by individuals prior to selection and that the optimal method of measuring brand personality for media products may be neither broad macro inventories nor highly context-specific micro measures but somewhere in between. This article discusses the construction of a unified scale of media brand personality that can measure the personality of movie, TV show, pop song, news, and video game brands. The results of a two-step study consisting of free-association task ( N = 1, 440) and factor structure formation survey of selected items ( N = 4, 967) suggest a three-factor structure consisting of aggression, heroism, and warmth. Communication, media management, and marketing ramifications of this scale and potential directions of future research are discussed.